SATISFACCIÓN DE LOS BENEFICIADOS DEL PROYECTO ATENCIÓN INTEGRAL PARA MEJORAR LA CALIDAD DE VIDA DE LAS PERSONAS ADULTAS MAYORES DEL CENTRO DIURNO DEL ADULTO MAYOR “RINCÓN DE AMOR” DEL CASMH EN EL PRIMER SEMESTRE DEL AÑO 2015 - Zúñiga Salinas, Jorge Geovanny (2017)
The main purpose of this thesis is to measure the level of "Satisfaction of the beneficiaries of the integral care project to improve the quality of life of the elderly adults of the CASMH Senior Center" Rincón de Amor "senior center in the first semester of the year 2015 "from the perception of the elderly, their relatives and the managers of the center. It includes a synthesis of the fundamental ideas of various authors about the quality care that the older adult should receive, taking into account that the staff who work in these centers must be properly trained and above all have a vocation to give them a quality care , So that adults sit in an environment similar to that of their family. The applied methodology is qualitative and quantitative, using for the collection of information instruments such as: direct observation, interviews, individual surveys, as well as scientific information that allowed to contrast it with the empirical one. The results show in detail the motivations, values, expectations, levels of satisfaction to go to the center, as well as the degree of dissatisfaction that currently lives. As a conclusion, it was found that older adults are mostly dissatisfied because the care they receive is not adequate, since they do not have a trained staff and adequate infrastructure according to their requirements. They express the need for better care, with an adequate operational staff, to provide their services by vocation but not for a salary since they need patience, understanding and care, to overcome the estrangement of their family since in some cases They feel forgotten and rejected, by their own.